All work and no play ; Where little things count ; On our own [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
Interview with working children, victims of child labor in Youngs Town and Capital Refinery in Cainta, Rizal. KY, an organization of the Graduate School Volunteer group in Ateneo work with cancer afflicted children. McKintosh Production on Les Miserables staged in the Philippines by Filipino performers.